2014
DOI: 10.1371/journal.pntd.0003325
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Drivers of the Epidemiology of Arthropod-Borne Viruses in Australia

Abstract: Arthropod-borne viruses are a major cause of emerging disease with significant public health and economic impacts. However, the factors that determine their activity and seasonality are not well understood. In Australia, a network of sentinel cattle herds is used to monitor the distribution of several such viruses and to define virus-free regions. Herein, we utilize these serological data to describe the seasonality, and its drivers, of three economically important animal arboviruses: bluetongue virus, Akabane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…; Melville ; Geoghegan et al . ). Indeed, the combined retrospective serological testing and subsequent virus genome characterization data from Kalumburu sentinel herd samples, further implicated the northern tip of Western Australia as a ‘hotspot’ for BTV emergence on the Australian mainland (Eagles et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Melville ; Geoghegan et al . ). Indeed, the combined retrospective serological testing and subsequent virus genome characterization data from Kalumburu sentinel herd samples, further implicated the northern tip of Western Australia as a ‘hotspot’ for BTV emergence on the Australian mainland (Eagles et al .…”
Section: Discussionmentioning
confidence: 97%
“…The present study reports that despite similar etiological features between SBV and AKV, both viruses have distinct selection profiles and the strength of selection is likely to be time-dependent. The estimated mutation rate and the overall x of the recently emerged SBV are considerably higher than those estimates of AKV, which has been causing sporadic outbreaks in ruminant populations across the temperate and tropical regions since 1970s (Geoghegan et al, 2014;Jun et al, 2012;Kessell et al, 2011;Kono et al, 2008;Lee et al, 2007;Oem et al, 2014Oem et al, , 2012Yamakawa et al, 2006). Such discrepancies could possibly be attributed to the differences in the timing of emergence of these two infectious viral pathogens.…”
Section: Discussionmentioning
confidence: 80%
“…Although both viruses have similar etiological features and host range, they exhibit distinct geographical distributions and emerge at different time points. While AKV is relatively older and has been causing sporadic outbreaks in the cattle industries across Asia, Australia, and Africa since 1970s (Geoghegan et al, 2014;Jun et al, 2012;Kessell et al, 2011;Kono et al, 2008;Lee et al, 2007;Oem et al, 2014Oem et al, , 2012Yamakawa et al, 2006), SBV was first reported in autumn 2011 in Germany (Hoffmann et al, 2012) and subsequently, spread across most of the European countries Chaintoutis et al, 2014;Doceul et al, 2013;Dominguez et al, 2014;Herder et al, 2012;van den Brom et al, 2012;Yilmaz et al, 2014). The two viruses have similar genomic features with three genomic segments, small (S), medium (M) and large (L) (Fischer et al, 2013).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…In 2011 there were three different strains of the virus isolated. In addition, the average number of seroconversions had a strong geographical component that reflects patterns of vector biology responsible for BEF virus transmission [23]. Furthermore, the lower neutralizing antibody titers in 2007 suggesting reduced immunity reflects the importance of population immunity for the control of BEFV [24].…”
Section: Discussionmentioning
confidence: 99%